Fatigue of four metallic materials under asynchronous loadings: Small cracks observation and fatigue life prediction. (January 2021) - Pejkowski, Łukasz; Seyda, Jan
Highlights: Small cracks on surfaces of fatigued specimens were observed. Shear damage mechanism was revealed for aluminum alloy and non-alloy steels. Austenitic stainless steel exhibited the tensile damage mechanism. Fatigue life prediction was performed based on six popular damage parameters. Correlation between the damage mechanism and the fatigue life prediction was noted. Abstract: This paper is a continuation of previously published work. It presents the results of small cracks observation on the surfaces of fatigued specimens subjected to multiaxial loadings. Specimens were manufactured from four materials: PA38-T6 aluminum alloy, E235 and E355 non-alloy steels, and X5CrNi18-10 austenitic steel. Based on the cracking analysis, it was found that the aluminum alloy and low-alloy steels exhibited shear damage mechanism, while the austenitic steel showed the tensile damage mechanism. Fatigue life prediction was performed based on six popular damage parameters. A correlation between the observed damage mechanism and the fatigue life prediction quality was noted.